2005
DOI: 10.1070/im2005v069n06abeh002295
|View full text |Cite
|
Sign up to set email alerts
|

Uniformization of strictly pseudoconvex domains. I

Abstract: It is shown that two strictly pseudoconvex Stein domains with real analytic boundaries have biholomorphic universal coverings provided that their boundaries are locally biholomorphically equivalent. This statement can be regarded as a higher dimensional analogue of the Riemann uniformization theorem.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…The domains D n t illustrate the relationship between the fundamental group of a smoothly bounded Stein domain and that of its (connected) boundary, which is important, for example, for the uniformization problem. Namely, if D is a smoothly bounded Stein domain, the fundamental groups π 1 (D) and π 1 (∂D) are isomorphic in complex dimensions ≥ 3, whereas in dimension 2 there exists a surjective homomorphism π 1 (∂D) → π 1 (D) and the fundamental group of ∂D can be larger than that of D (see [14] for a detailed discussion of these facts). Indeed, as we observed above,…”
Section: The Family M N Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The domains D n t illustrate the relationship between the fundamental group of a smoothly bounded Stein domain and that of its (connected) boundary, which is important, for example, for the uniformization problem. Namely, if D is a smoothly bounded Stein domain, the fundamental groups π 1 (D) and π 1 (∂D) are isomorphic in complex dimensions ≥ 3, whereas in dimension 2 there exists a surjective homomorphism π 1 (∂D) → π 1 (D) and the fundamental group of ∂D can be larger than that of D (see [14] for a detailed discussion of these facts). Indeed, as we observed above,…”
Section: The Family M N Tmentioning
confidence: 99%
“…Indeed, otherwise by results of [14] the universal cover of the domain D n t would be biholomorphic to the unit ball B n ⊂ C n . Since D n t is simply connected, this would imply that D n t is biholomorphic to B n , which is impossible since D n t is not contractible.…”
Section: Remark 22mentioning
confidence: 99%
“…As a generalization of Chern-Ji's theorem ( [2]), Nemirovskii-Shaffikov proved in [11,12] that a strongly pseudoconvex domain Ω with C ∞ -smooth boundary is covered by the unit ball if every boundary point is spherical in the sense that all the CR invariants vanish identically on ∂Ω (cf. [3]).…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the Ramadanov conjecture implies the Cheng conjecture. In particular it follows that the Cheng conjecture holds in dimension two.In this brief note we use our uniformization result from [10,11] to extend the work of Fu and Wong [7] on the relationship between two long-standing conjectures about the behaviour of the Bergman metric of a strictly pseudoconvex domain in C n , n ≥ 2. …”
mentioning
confidence: 99%